Measuring the Effectiveness of Border Security Between Ports-of-Entry - Willis, Henry H. (RAND Corporation, 2010)
This report offers research and recommendations on ways to measure the overall efforts of the national border-security enterprise between ports of entry. Focusing on three missions--illegal drug control, counterterrorism, and illegal migration--this report recommends ways to measure performance of U.S. border-security efforts in terms of interdiction, deterrence, and exploiting networked intelligence.